IMF Staff Papers, Volume 54, No. 3. (IMF Staff Papers; IMF Staff Papers ;, 2007)
This issue features a timely paper by Vladimir Klyuev and Paul Mills on the role of personal wealth and home equity withdrawal in the decline in the U.S. saving rate. Lusine Lusinyan and Leo Bonato explain how work absence in 18 European countries affects labor supply and demand. And a paper by Paolo Manasse (University of Bologna) entitled "Deficit Limits and Fiscal Rules for Dummies" examines fiscal frameworks.